A New δ Chain Variant, Hb A2-Tunis [δ46(CD5)Gly → Glu; HBD: c.140G>A], Observed in a Tunisian Family in Association with a Compound Heterozygosity for Hb C [β6(A3)Glu → Lys; HBB: c.19G>A] β0-Thalassemia [IVS-I-1 (β143, G>A); HBB: c.92+1G>A]. (April 2014) - Moumni, Imen; Zorai, Amine; Mahjoub, Sonia; Mosbahi, Ikbel; Chaouechi, Dorra; Benromdhane, Neila; Abbes, Salem
Abstract We describe a new δ-globin variant, Hb A2-Tunis [δ46(CD5)Gly → Glu; HBD: c.140G>A]. This hemoglobin (Hb) variant displayed a faster electrophoretic mobility than normal Hb A2 and was expressed at 3.2%. The molecular defect was characterized by DNA sequencing analysis. Hb A2-Tunis was found in a carrier of a β0-thalassemia (β0-thal) [IVS I-1 (β143, G>A); HBB: c.92 + 1G>A] and Hb C [β6(A3)Glu → Lys; HBB: c.19G>A], presenting with a normal Hb A2 level. Phenotype and genotype investigations revealed that the patient has a total Hb A2 level of 7.1% that was expected for a β-thalassemia (β-thal) minor carrier.